The ICT Revolution: Opportunities and Risks for the Mezzogiorno - Elena Bellini; Gianmarco I.P. Ottaviano; Dino Pinelli (Fondazione Eni Enrico Mattei (FEEM), 2003)
The question of the spatial impacts of Information and Communication Technology (ICT) has animated intellectual and policy debate for a long time. At the beginning of the 1990s the advent of the Internet brought a new surge of debate: it was argued that the Internet would free the economy from the constraints of geography (Cairncross, 1997), bringing about a more even economic landscape. New opportunities seemed to arise for the poor regions in peripheral areas such as the Italian Mezzogiorno. However, this contrasts sharply with the popular view of, for example, Silicon Valley, a congested area where world-class ICT and high-tech industries cluster together. In theory, geographical agglomeration of economic activities results as an equilibrium solution of a tension between centripetal and centrifugal forces. ICT has the potential to alter the balance between centripetal and centrifugal forces and therefore the final equilibrium solution. Literature shows that, from a theoretical point of view, there are a number of counterbalancing effects rather than a one directional trend. The question therefore begs empirical research. This paper investigates the effect of the ICT revolution on industrial locational patterns across Italian provinces. It shows that the increasing use of ICT in the economy may indeed lead to greater dispersion of economic activity, i.e. less regional disparities. On the other hand, there is evidence that the parallel shift towards more knowledge- and skill-intensive activities might counterbalance this dispersion effect.
Keywords: R0; O3; 330; ICT; Regional cohesion; Convergence; Informationstechnik; Räumliche Verteilung; Wirtschaftliche Konvergenz; Agglomerationseffekt; Italien; Italien (Süd)